2018
DOI: 10.1038/s41598-018-21815-x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β with isomerized Asp7 cytotoxicity is coupled to protein phosphorylation

Abstract: Neuronal dysfunction and loss associated with the accumulation of amyloid-β (Aβ) in the form of extracellular amyloid plaques and hyperphosphorylated tau in the form of intraneuronal neurofibrillary tangles represent key features of Alzheimer’s disease (AD). Amyloid plaques found in the brains of AD patients are predominantly composed of Aβ42 and its multiple chemically or structurally modified isoforms. Recently, we demonstrated that Aβ42 with isomerised Asp7 (isoAβ42) which is one of the most abundant Aβ iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Interestingly, it has been found that iso -Asp-7 Aβ 42 compared to wild-type Aβ 42 led to significantly increased phosphorylation of proteins, including tau (MAPT) from SH-SY5Y neuroblastoma cell-culture models. 72 Accumulation of iso-aspartate in proteins is known to be lethal in the PIMT (protein iso-aspartate methyltransferase) deficient mouse, suffering from progressive epileptic seizures. 73 , 74 Soluble Aβ oligomers isolated from Alzheimer’s disease brains have been shown to induce hyperexcitability in individual neurons and neuronal circuits 75–77 Induction of hyperexcitability has been invoked to explain the clinical observation that there is a significantly higher incidence of epilepsy in Alzheimer’s disease patients compared to age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been found that iso -Asp-7 Aβ 42 compared to wild-type Aβ 42 led to significantly increased phosphorylation of proteins, including tau (MAPT) from SH-SY5Y neuroblastoma cell-culture models. 72 Accumulation of iso-aspartate in proteins is known to be lethal in the PIMT (protein iso-aspartate methyltransferase) deficient mouse, suffering from progressive epileptic seizures. 73 , 74 Soluble Aβ oligomers isolated from Alzheimer’s disease brains have been shown to induce hyperexcitability in individual neurons and neuronal circuits 75–77 Induction of hyperexcitability has been invoked to explain the clinical observation that there is a significantly higher incidence of epilepsy in Alzheimer’s disease patients compared to age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of isoD7-Aβ in amyloid plaques can be associated with the processes of spontaneous protein aging ( Moro et al, 2018 ), while the formation of pS8-Aβ was attributed to the ecto-PKA activity ( Kumar et al, 2011 ). Both isoforms of Aβ were suggested to play a role in AD pathogenesis ( Kozin et al, 2016 ; Jamasbi et al, 2017 ; Kugaevskaya et al, 2018 ; Zatsepina et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Asn residues show very fast succinimide formation comparing Asp residues [ 18 ]; consequently, isoAsp residues are rapidly accumulated in AβP. The synthetic AβPs in which Asp 7 or Asp 23 is substituted for isoAsp residue show the enhancement of neurotoxicity [ 82 ] or the acceleration of fibril formation [ 83 ], respectively. These results suggest that both FAD mutations in AβP accelerate amyloid fibril formation in the brain of patients owing to the fast generation of the isoAsp residue in the AβP of Tottori and Iowa.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AβP 1–42 (D7isoD) acts as a trigger for the formation of dense-core amyloid plaques in the APP transgenic mouse brain [ 81 ]. The phosphorylation of proteins such as tau, tubulins, and matrin 3 is also accelerated by AβP 1–42 (D7isoD) when the peptide is introduced to cultured cells [ 82 ]. The effect of Asp racemization on the fibril formation has also been examined using synthetic peptides.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%